AN ESTHETIC EXPERIENCE IN CONTINUING TEACHER TRAINING IN SCHOOL - Goncalves, Rosy [UNESP]; Chaluh, Laura Noemi [UNESP] (Univ Metodista Piracicaba-unimep, 2021)
The present work is an excerpt from a master's research that had as its general objective to analyze the training processes triggered in the context of the Collective Pedagogical Work Hours (HTPCs) and that had as a guide the aesthetic experiences. In this work we discuss the formation of teachers in the school context involving the literary language, the cinematographic language and the visual language, propellers of aesthetic experiences. We socialize the concerns and practices promoted by a beginning coordinating teacher concerned with the continuing education of teachers in the context of a municipal school for Early Childhood and Elementary Education in the city of Rio Claro/SP. It is narrative research (LIMA; GERALDI; GERALDI, 2015) that took as an object of study the practices of continuing education instituted by the referred coordinating teacher. To compose this work, we used the writings of the personal logbook of the coordinating teacher; records of teachers and management staff contained in the HTPCs Memories Folder and HTPCs assessment sheets. To develop the process of interpreting the data, we took inspiration from the evidential paradigm. The research revealed that the aesthetic experience favored a humanizing formative proposal and implied in the formation a new meaning of the coordinator professor's own performance.
Keywords: COORDINATING TEACHER; CONTINUING EDUCATION; AESTHETIC EXPERIENCE